The association of alcohol and alcohol metabolizing gene variants with diabetes and coronary heart disease risk factors in a white population. - Lise Lotte N Husemoen (Public Library of Science (PLoS), 2010)
Background Epidemiological studies have shown a J- or U-shaped relation between alcohol and type 2 diabetes and coronary heart disease (CHD). The underlying mechanisms are not clear. The aim was to examine the association between alcohol intake and diabetes and intermediate CHD risk factors in relation to selected ADH and ALDH gene variants. Methodology/principal findings Cross-sectional study including 6,405 Northern European men and women aged 30-60 years from the general population of Copenhagen, Denmark. Data were collected with self-administered questionnaires, a physical examination, a 2 hour oral glucose tolerance test, and various blood tests. J shaped associations were observed between alcohol and diabetes, metabolic syndrome (MS), systolic and diastolic blood pressure, triglyceride, total cholesterol, and total homocysteine. Positive associations were observed with insulin sensitivity and HDL cholesterol, and a negative association with insulin release. Only a few of the selected ADH and ALDH gene variants was observed to have an effect. The ADH1c (rs1693482) fast metabolizing CC genotype was associated with an increased risk of impaired glucose tolerance (IGT)/diabetes compared to the CT and TT genotypes. Significant interactions were observed between alcohol and ADH1b (rs1229984) with respect to LDL and between alcohol and ALDH2 (rs886205) with respect to IGT/diabetes. Conclusions/significance The selected ADH and ALDH gene variants had only minor effects, and did not seem to markedly modify the health effects of alcohol drinking. The observed statistical significant associations would not be significant, if corrected for multiple testing.